2014
DOI: 10.1118/1.4890589
|View full text |Cite
|
Sign up to set email alerts
|

Process‐based quality management for clinical implementation of adaptive radiotherapy

Abstract: Purpose: Intensity-modulated adaptive radiotherapy (ART) has been the focus of considerable research and developmental work due to its potential therapeutic benefits. However, in light of its unique quality assurance (QA) challenges, no one has described a robust framework for its clinical implementation. In fact, recent position papers by ASTRO and AAPM have firmly endorsed pretreatment patient-specific IMRT QA, which limits the feasibility of online ART. The authors aim to address these obstacles by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 23 publications
(30 reference statements)
2
46
0
1
Order By: Relevance
“…Table III gives the total number of subprocesses, process steps, and potential failure modes for all three centers. The number of process steps found in this study (47-56) is comparable to those reported by Ford et al, who reported 62 process steps for their study, 4 Noel et al, who reported 52 process steps for their study, 5 and Masini et al, who reported 73 process steps for their study. 6 Although the results presented by Ford et al and Noel et al correspond to analyses performed for external beam treatment, the differences between their studies and the present study are not expected to be very different recognizing the subtle differences that exist among all these studies.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Table III gives the total number of subprocesses, process steps, and potential failure modes for all three centers. The number of process steps found in this study (47-56) is comparable to those reported by Ford et al, who reported 62 process steps for their study, 4 Noel et al, who reported 52 process steps for their study, 5 and Masini et al, who reported 73 process steps for their study. 6 Although the results presented by Ford et al and Noel et al correspond to analyses performed for external beam treatment, the differences between their studies and the present study are not expected to be very different recognizing the subtle differences that exist among all these studies.…”
Section: Resultssupporting
confidence: 86%
“…Failure modes with severity index S ≥ 7 represented 68% of the total failure modes/cause combination found for center III, 62% for center II, and 45% for center I. Similar results for detectability D ≥ 5 were found to be 7.6% (49/644) for center I, 5 found for center I, 9.3% (47/506) for center II, and 8.0% (55/689) for center III. The factors O and D both depend on the causes of failure, but D also depends additionally on the detection mechanisms existing at a radiotherapy center.…”
Section: Resultssupporting
confidence: 68%
“…In contrast to the end‐to‐end test quality assurance procedures, this system identifies the contribution of the different components, and highlights particularly the components that have the largest uncertainties contributions which can be fixed or reduced in the specific clinical application. Furthermore, this approach may be useful in failure mode and effect analysis used by forthcoming AAPM Task Group‐100, 24 , 25 in which the procedure is broken into different processes and each process is divided into subprocesses where the failure modes and large uncertainty sources can be identified and quantified. Once a process or subprocess with frequent failure modes or large errors is identified, integrated quality control procedures can be implemented whereby more frequent checking on this particular process is performed to achieve accurate and safe operation.…”
Section: Discussionmentioning
confidence: 99%
“…An FMEA for both the MTP and ACP was performed, compared, and evaluated for robustness. Our group has successfully employed this method of appraisal in the past . Using this approach, FMEA assesses each step of every automated TPS commissioning test as well as that of the current recommended tests in MPPG 5.a.…”
Section: Introductionmentioning
confidence: 99%